THE STATE AS AN ACTOR OF MODERN INTERNATIONAL RELATIONS (British Journal of Global Ecology and Sustainable Development, 2023)
The implementation of a unified state policy in the field of modern international political and economic relations ensures the further development of economic and financial cooperation between Uzbekistan and foreign countries, international economic organizations and financial institutions, and other subjects of international law on a reciprocal basis. profitable basis. Therefore, the economic reforms carried out in our country are aimed at securing Uzbekistan's place in the world economic system in a short time and equal cooperation with all countries of the world.